Developing a low-cost system for 3d data acquisition - Kossieris, S.; Kourounioti, O.; Agrafiotis, Panagiotis; Georgopoulos, Andreas (My University, 2017)
In this paper, a developed low-cost system is described, which aims to facilitate 3D documentation fast and reliably by acquiring the necessary data in outdoor environment for the 3D documentation of facades especially in the case of very narrow streets. In particular, it provides a viable solution for buildings up to 8-10m high and streets as narrow as 2m or even less. In cases like that, it is practically impossible or highly time-consuming to acquire images in a conventional way. This practice would lead to a huge number of images and long processing times. The developed system was tested in the narrow streets of a medieval village on the Greek island of Chios. There, in order to by-pass the problem of short taking distances, it was thought to use high definition action cameras together with a 360¢camera, which are usually provided with very wide-angle lenses and are capable of acquiring images, of high definition, are rather cheap and, most importantly, extremely light. Results suggest that the system can perform fast 3D data acquisition adequate for deliverables of high quality.
Keywords: 360° camera; Action camera; Facades; Low-cost 3D; Narrow streets; Orthoimage